IMPLEMENTASI KEBIJAKAN PERDA NOMOR 04 TAHUN 2005 DALAM UPAYA MEMFUNGSIKAN LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) DI WILAYAH KECAMATAN BEKASI UTARA KOTA BEKASI - Darma Priatna; Sudiono - (Governance, 2021)
The institution is a government partner.The existence of Community Empowerment Institutions does not show its function, As an institution is only complementary, lacks role, is still weak and has not been accepted by the community, the institution is only a symbol, has not yet had an initiative, has not been able to mobilize community self- help in development.This thesis research puts forward the theory of George W. Edward III. He gave four key points in looking at the implementation of policies, namely First Communication, Both Resources, Third Disposition and the fourth Structure of Bureaucracy. The use of methods in this study using qualitative descriptive methods. In this study using a sample with a community Purposive sampling technique in North Bekasi District. Data collection techniques used in the form of observation techniques, interviews and questionnaires or questionnaires. Communication between the government and administrators of the Society and Community Empowerment Institutions has proceeded according to provisions. Resource. Already applied in the institution. according to the duties and functions of the institution. Disposition aspect in the institution's activity program, according to the trial and skills possessed. Bureaucratic structure is a series of activities according to the Standard Operating Prosedures (SOPs). Regular and conducive working mechanisms for Community Empowerment Institutions are in accordance with regional regulations and this institution can function as a forum for community participation.